Sirtuin 1 reduces hyaluronan synthase 2 expression by inhibiting nuclear translocation of NF-κB and expression of the long-noncoding RNA HAS2–AS1 - Caon, Ilaria (2020)
Hyaluronan (HA) is one of the most prevalent glycosaminoglycans of the vascular extracellular matrix (ECM). Abnormal HA accumulation within blood vessel walls is associated with tissue inflammation and is prominent in most vascular pathological conditions such as atherosclerosis and restenosis. Hyaluronan synthase 2 (HAS2) is the main hyaluronan synthase enzyme involved in HA synthesis and uses cytosolic UDP-glucuronic acid and UDP-GlcNAc as substrates. The synthesis of UDP-glucuronic acid can alter the NAD+/NADH ratio via the enzyme UDP-glucose dehydrogenase, which oxidizes the alcohol group at C6 to the COO- group. Here, we show that HAS2 expression can be modulated by sirtuin 1 (SIRT1), the master metabolic sensor of the cell, belonging to the class of NAD+-dependent deacetylases. Our results revealed the following. 1) Treatments of human aortic smooth muscle cells (AoSMCs) with SIRT1 activators (SRT1720 and resveratrol) inhibit both HAS2 expression and accumulation of pericellular HA coats. 2) Tumor necrosis factor α (TNFα) induced HA-mediated monocyte adhesion and AoSMC migration, whereas SIRT1 activation prevented immune cell recruitment and cell motility by reducing the expression levels of the receptor for HA-mediated motility, RHAMM, and the HA-binding protein TNF-stimulated gene 6 protein (TSG6). 3) SIRT1 activation prevented nuclear translocation of NF-κB (p65), which, in turn, reduced the levels of HAS2–AS1, a long-noncoding RNA that epigenetically controls HAS2 mRNA expression. In conclusion, we demonstrate that both HAS2 expression and HA accumulation by AoSMCs are down-regulated by the metabolic sensor SIRT1.